Growth and development of black currant depending on the use of mulching and irrigation - Кучер, М. Ф.; Постоленко, Л. В. (Scientific Progress & Innovations, 2016)
The results of estimation of total one-year plants’ increase of sorts of black currant are resulted and estimation of their productivity is conducted at mulching of stripes near bushes and use of irrigation. It is set as a result of researches, that at all explored sorts of the use of mulching materials in stripes near bushes bars was instrumental in the substantial increase of total one-year increase both in variants with the use of tiny irrigation and without irrigation on a background of control variant – black pair. The greatest productivity of planting of black currant provides the compatible use of tiny irrigation and mulching materials.